2023
DOI: 10.1055/a-2018-1612
|View full text |Cite
|
Sign up to set email alerts
|

Can white-light endoscopy or narrow-band imaging avoid biopsy of colorectal endoscopic mucosal resection scars? A multicenter randomized single-blind crossover trial

Abstract: Background and aims: Current guidelines suggest that routine biopsy of post-endoscopic mucosal resection (EMR) scars can be abandoned, provided that a standardized imaging protocol with virtual chromoendoscopy is used. However, few studies have examined the accuracy of advanced endoscopic imaging, such as Narrow Band Imaging (NBI) versus White Light Endoscopy (WLE) to predict histological recurrence. We aimed to assess whether NBI accuracy is superior to WLE and whether one or both techniques can replace biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this issue of Endoscopy, João et al report on a randomized controlled trial comparing HD-WLE with NBI for the prediction of histological recurrence after EMR of lesions ≥ 20 mm [10]. The study included 203 scars and RRA was confirmed histologi-cally in 29.6 %.…”
mentioning
confidence: 99%
“…In this issue of Endoscopy, João et al report on a randomized controlled trial comparing HD-WLE with NBI for the prediction of histological recurrence after EMR of lesions ≥ 20 mm [10]. The study included 203 scars and RRA was confirmed histologi-cally in 29.6 %.…”
mentioning
confidence: 99%
“…enhanced imaging [20]. Thus, abandoning this practice would further reduce forceps use in our practice (Table 3).…”
Section: Manuscriptmentioning
confidence: 99%
“…We performed large numbers of cold forceps biopsies of EMR scars to as we previously showed this approach increase d identification of residual polyp after EMR [7]. Recent studies found routine biopsy can be replaced by detailed inspection of the EMR scars using high definition enhanced imaging [2020 20 ]. Thus, abandoning this practice would further reduce forceps use in our practice (Table 3).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A recent multicentre single-blind cross-over trial (n = 203) to compare NBI and high definition white light for the assessment of recurrence or residual adenoma at a post-EMR scar reported a negative predictive value (NPV) > 90% (NPV 96% using NBI, NPV 93% using high definition white light) [58]. Use of NBI was not superior to high definition white light (p = 0.06) [58]. Expert consensus is that a biopsy is not needed for a bland scar with a uniform pit pattern [57].…”
Section: Surveillancementioning
confidence: 99%